Midiendo la complejidad de la red cósmica (2020)
The cosmic web is the filamentary pattern in the spatial distribution of galaxies at large scales in the Universe. An alternative to descrbie these patterns is the constructions of graphs whose nodes are the galaxies. The statistical description of these graphs can be done in multiple ways. In this work we explore the statistical complexity on one of these graphs to characterize the cosmic web. This complexity is calculated on the probability of a node having n conections P(n). We compute this complexity as the product between the Shannon entropy S(P) and the Jensen-Shannon divergence between P(n) and the connection distribution of a random set of points R(n). With this definition we study the complexity of the cosmic web from simulations and observations. Our results show that complexity is a statistic capable of distinguishing simulated cosmic webs from one built from observations.